Posttransplantation anemia in kidney transplant recipients: A retrospective cohort study. Issue 32 (August 2017) - Gafter-Gvili, Anat; Ayalon-Dangur, Irit; Cooper, Lisa; Shochat, Tzippy; Rahamimov, Ruth; Gafter, Uzi; Mor, Eytan; Grossman, Alon
Abstract : Abstract: We sought to assess the frequency and predictors of early and late posttransplantation anemia (PTA). In addition, we aimed to assess the outcomes of patients with anemia and to assess the impact of anemia on mortality, graft function, and graft failure. Patients who underwent kidney transplantation in a single center during a 4-year period were included. Predictors associated with the development of anemia at 6 months (early PTA) or 2 years (late PTA) were evaluated in a univariate and multivariate analyses. The effects of anemia and other variables on mortality and graft function were assessed. A total of 266 kidney transplant recipients were included. The prevalence of PTA at 6 months (early PTA) was 51.3% and at 2 years (late PTA) was 36.6%. Female sex was significantly associated with early PTA. Patients with early PTA proceeded to late PTA. Patients with both early and late PTA had a higher mortality rate at 4 years compared to patients without anemia. On multivariable analysis, lower Hb at 2 years posttransplantation (hazard ratio [HR] 0.716, 95% confidence intervals [CI] 0.541–0.948, for every increment of 1 g/dL) was significantly associated with mortality. Patients with late PTA suffered a decline in eGFR compared to patients without anemia ( P  = .026). Furthermore, a lower Hb at 2 years posttransplantation was also associated with graft failure (HR 0.775, 95% CI 0.619–0.969, for every increment of 1 g/dL). Post-transplantation anemia is significantly associated with late mortality, with a decline in graft function and with an increased incidence of graft failure.